Potencial futuro e investigacion necesaria para el incremento de la yuca - Cock, James H.; Lynam, John K. (International Center for Tropical Agriculture, 1979)
The possibilities of underdeveloped countries to satisfy their needs for food and to improve the standard of Eving through cassava production are analyzed. The following aspects are studied: potential cassava production (current and potential situation), general research policies and areas (var. development, pest control, agronomic practices, and multiple cropping), transfer of technology, utilization of cassava in human and animal nutrition and in the production of alcohol. Tables are included on potential yields, production costs, and price-elasticity, and income in Indonesia. (CIAT)